An Analysis of Annual Tax Return Filing Compliance among Civil Servant Teachers within the Jember Regency Education Department - Sulton Maulana Ibrahim; Divanti Cinta Aulia Putri; Ari Fahimatussyam Putra Nusantara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the compliance of Annual Tax Return (SPT Tahunan) reporting among civil servant teachers (ASN teachers) within the Department of Education of Jember Regency. The research focuses on understanding the quality of tax compliance, the factors influencing compliance behavior, and the role of school operators in the reporting process. This study employed a descriptive qualitative approach to explore the experiences, perceptions, and obstacles faced by ASN teachers in fulfilling their tax obligations. Data were collected through in-depth semi-structured interviews and documentation involving ASN teachers, school operators, and related officials within the Department of Education. The collected data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that the compliance of ASN teachers in reporting Annual Tax Returns has been formally achieved and generally completed on time. However, such compliance is predominantly driven by administrative obligations, sanctions, and professional allowance requirements rather than voluntary tax awareness. The study also reveals a significant dependence of teachers on school operators due to limited tax literacy and difficulties in using digital tax systems, especially during the transition from DJP Online to Coretax. In addition, tax socialization programs conducted by the tax office and the Department of Education have contributed positively to improving reporting orderliness, although their implementation has not yet reached all teachers directly.